ANGIOEDEMA; AN UNREPORTED ADVERSE EFFECT OF PITAVASTATIN - Naz, Saba; Saleem, Muhammad Wali; Haider, Agha Waqar (Journal of Ayub Medical College Abbottabad, 2018)
Angioedema is a life-threatening reaction characterized by swelling of the face, lips, tongue or larynx. Known adverse effects of Pitavastatin do not include angioedema. We report first case of a 55-year-old Asian male developing post exposure angioedema to 2 mg Pitavastatin. Note that the patient showed no history of hypersensitivity. Relationship between Pitavastatin and angioedema was assessed by Naranjo scale. Keywords: Angioedema; Pitavastatin; Allergic reaction; Statin, Adverse effects